The Harms of a Penal Colony - Strong, Justin (The Hastings Center report, 2019)
More than just a jail, Rikers has become a site of shifting discourse on punishment and justice in the United States. In the book Life and Death in Rikers Island, Homer Venters argues that the systematic failures of jails to provide appropriate safety and care constitute human rights violations and public health risks. The former chief medical officer and commissioner of correctional health services for the NYC Health and Hospitals system, Venters offers critical insight on the Rikers jail system. “Because jails are chaotic and concealed from outside view,” he asserts, “we only become aware of them when very bad outcomes occur, such as deaths.” Life and Death's success lies in how it blends Venters's experiences on the ground as a health care professional with the empirical data he's been able to collect and analyze over the tenure of his career. According to Venters, all suicides, homicides, and accidental deaths in jail are jail attributable, as they reflect system-wide failures in safety.